Fatores antecedentes na geração de novos negócios: estudo de casos no Brasil - Kahn, Ricardo (2012)
This paper examines the efforts oriented to the internal generation of new businesses in Brazilian subsidiaries of multinational corporations. In order to reach that, it uses an exploratory research, in form of a multiple case study, carried out with four projects, in three different companies. The research adds empirical evidences, which could be later used by the academy on the development of theories, or by practitioners, as references to best practices. The analysis of the cases is based on the literature produced around the concept of corporate venturing, pointed out as one of the expressions of the corporate entrepreneurship. The study identifies considerable differences in the approach of the analyzed companies. It depicts cases of organizational separation between the venturing unit to the traditional business, and others, where it finds traces of organizational ambidexterity. It notes the existence of structured processes, encompassing stages as ideas prospection and incubation, besides other simplified ones, developed ad- hoc for specific projects. Additionally, the study points out indications of strategic logics oriented both for the exploration and the exploitation. Finally, it presents some particularities detected as consequences of the development being held in the Brazilian environment.